Developing Human-Centered Urban Digital Twins for Community Infrastructure Resilience: A Research Agenda. (May 2023) - Ye, Xinyue; Du, Jiaxin; Han, Yu; Newman, Galen; Retchless, David; Zou, Lei; Ham, Youngjib; Cai, Zhenhang
Urban digital twins (UDTs) have been identified as a potential technology to achieve digital transformative positive urban change through landscape architecture and urban planning. However, how this new technology will influence community resilience and adaptation planning is currently unclear. This article: (1) offers a scoping review of existing studies constructing UDTs, (2) identifies challenges and opportunities of UDT technologies for community adaptation planning, and (3) develops a conceptual framework of UDTs for community infrastructure resilience. This article highlights the need for integrating multi-agent interactions, artificial intelligence, and coupled natural–physical–social systems into a human-centered UDTs framework to improve community infrastructure resilience.